Probabilistic Assessment of Buildings Subjected to Multi-Level Earthquake Loading Based on the PBSD Concept - J. Guadalupe Monjardin-Quevedo; Federico Valenzuela-Beltran; Alfredo Reyes-Salazar; J. Martin Leal-Graciano; Xochitl G. Torres-Carrillo; J. Ramon Gaxiola-Camacho (Buildings, 2022)
An alternative probabilistic assessment of buildings excited by multi-level seismic loading is presented in this paper. This evaluation is developed for both steel and reinforced concrete buildings using the Performance-Based Seismic Design (PBSD) concept. The methodology implements Probability Density Functions (PDFs) of inter-story drifts to extract structural risk in terms of the reliability index. Ten buildings of steel and reinforced concrete, respectively, are designed considering different locations in Mexico. Then, each structure is excited by ground motions representing different earthquake intensity levels for three performance levels: immediate occupancy, life safety, and collapse prevention. The deterministic seismic response of buildings is extracted using the finite element software OpenSees. Based on the results, it can be stated that the probabilistic assessment technique represents an efficient approach for extracting the seismic risk of structures using PDFs of inter-story drifts. Lastly, it is demonstrated that the evaluation of buildings following PBSD is a step in the right direction, moving from traditional deterministic design concepts to probabilistic philosophies.